Íons fluoreto em águas subterrâneas: monitoramento e remoção por eletrocoagulação-flotação e adsorção com resíduos de tabaco - Somavilla, Ezequiel Andrei (2020)
The excess of fluoride ions (F-) is a problem in the quality of water supply because they can trigger human health problems such as dental and skeletal fluorosis. Removal of F- to concentrations predicted by potability standards (less than 1.5 mg F-L-¹) can be made possible by the use of unit electrocoagulation-flotation (ECF) operations and adsorption. The main objective of this dissertation was to contextualize the problem of F- in water, groundwater monitoring and consequently propose and study defluoridation operations, evaluating the best-operating conditions of electrocoagulation-flotation and the development of adsorbent for adsorption. Initially, the dependence of groundwater resources was presented, and the General Monitoring Index (IGM) showed that in 2018 in Brazil, the average water quality sampling was 1.3 samples per 1,000 inhabitants. Besides, about 489 samples were performed due to reporting, disasters or F- outbreaks, with dilution being the most used technique to reduce F- concentrations. In well water monitoring at the university, mean concentrations of 2.7 mgF-L-¹ were found, and at school 3.8 mgF-L-¹, accompanied by high concentrations of other parameters. As an alternative to defluoridation, ECF with school water samples completely removed at F- concentrations, with the best conditions having a pH below 6.2, reaction times greater than 20 minutes, any value being current density ensures a minimum efficiency of 95%. The removal of F- in aluminum hydroxide flakes was the identified defluoridation mechanism, and a negative aspect is the residual aluminum concentrations in the treated water were above the potability limit. Finally, it is concluded that ECF is not fully sufficient to potable groundwater, however, for defluoridation is an efficient and viable alternative. For adsorption, a tobacco residue-supported Al-Ca-Zn trimetallic composite (Al-Ca-Zn-tab) was synthesized as an alternative to using an agricultural residue from the F- contamination chain for defluoridation. In adsorption studies, F- removal efficiencies were up to 71.7%, with actual accumulations of up to 2.78 mg g-¹, and maximum accumulations of 13.59 mg g-1. The most suitable isotherm model was Freundlich, obtaining kF of 0.1336 (mg g-¹) (L mg-¹) (1 n-¹), n of 1.13, R² of 0.9978 and ARE 5.1%. The General Order kinetic model was the best fit, with kn of 0.193 min-¹, qn of 1.15 mg g-¹, n of 7.139, R² of 0.9881 and ARE of 5.21. Besides, through the thermodynamic analysis, it was found a predominance of physisorption phenomena and exothermic process, obtaining ΔG ° of -8.55 kJ mol-¹, ΔH ° of -1.21 kJ mol-¹, ΔS ° of 0.023 kJ mol-¹. The proposed adsorption mechanism is based on the ion exchange of surface hydroxyl groups, as well as electrostatic interactions due to bi and trivalent cations. Thus, Al-Ca-Zn-tab adsorbent proved to be an efficient alternative in the removal of fluoride ions from the water supply. Finally, with this work, we tried to present the problem of F- in waters, for the purpose of developing efficient defluoridation technologies. Consequently, we seek to contribute to the reduction of cases of fluorosis and other problems arising from exposure to the risk of excessive consumption of F-, thus helping to meet the United Nations Sustainable Development Goals (SDGs).